2010
DOI: 10.1515/jpm.2009.140
|View full text |Cite
|
Sign up to set email alerts
|

Retinol binding protein 4 – a novel association with early-onset preeclampsia

Abstract: Objective: Dysregulation of maternal circulating adipokines has been implicated in several ''great obstetrical syndromes'' including preeclampsia (PE), small-for-gestational age (SGA) neonate and fetal death (FD). It has been suggested that adipokines provide a molecular link between metabolic derangements and inflammatory response in complicated pregnancies. Retinol binding protein 4 (RBP4), a novel adipokine, plays a role in obesity-related disorders, as well as in the regulation of the immune response. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 143 publications
(155 reference statements)
5
41
0
Order By: Relevance
“…The simple correlation model showed a negative relationship between maternal RBP4 levels and birth weights, but this correlation disappeared after adjustment for maternal age, maternal insulin levels, maternal BMI, and cord serum RBP4 and insulin (table 2). This finding is consistent with a recent study by Vaisbuch et al [27] who argued that there is no significant difference in maternal plasma RBP4 levels between women with fetuses small for their gestational age and those with fetuses appropriate for their gestational age. However, a recent study conducted by Mazaki-Tovi et al [28] reported that mothers without gestational DM but with large for their gestational age neonates had a higher maternal plasma concentration of RBP4 than women with appropriate for their gestational age newborns.…”
Section: Discussionsupporting
confidence: 93%
“…The simple correlation model showed a negative relationship between maternal RBP4 levels and birth weights, but this correlation disappeared after adjustment for maternal age, maternal insulin levels, maternal BMI, and cord serum RBP4 and insulin (table 2). This finding is consistent with a recent study by Vaisbuch et al [27] who argued that there is no significant difference in maternal plasma RBP4 levels between women with fetuses small for their gestational age and those with fetuses appropriate for their gestational age. However, a recent study conducted by Mazaki-Tovi et al [28] reported that mothers without gestational DM but with large for their gestational age neonates had a higher maternal plasma concentration of RBP4 than women with appropriate for their gestational age newborns.…”
Section: Discussionsupporting
confidence: 93%
“…So far, we have found only a few reports about the relationship between RBP4 and preeclampsia. Two studies demonstrated that the RBP4 level was increased in obese patients with preeclampsia compared with normal controls [20,21], and our previous report demonstrated a significant increase of RBP4 in late onset patients with preeclampsia compared with normal late pregnancy controls [22]. In contrast, Stephan et al [23] observed no significant difference in RBP4 levels between patients with preeclampsia and normal control subjects, but all the patients in their study were lean and showed early-onset preeclampsia.…”
Section: Discussionmentioning
confidence: 65%
“…Previously plasma RBP4 levels were found to increase with increasing TG levels [6,27,28]. On the contrary, in a recent study no association was reported between maternal RBP4 levels and prepregnancy BMI, birth weight, parameters of insulin resistance and TG levels [29]. Higher maternal plasma levels of RBP4 were reported to be associated with larger neonates both in women with and without gestational diabetes mellitus [5], high maternal RBP4 concentrations were attributed to maternal glucose metabolism.…”
Section: Retinol-binding Protein 4 Levels Are Related To Maternal Trimentioning
confidence: 90%